Models for Predicting Time to Sputum Conversion Among Multi-Drug Resistant Tuberculosis Patients in Lagos, South–West Nigeria - Akinsola, Oluwatosin J.; Yusuf, Oyindamola B.; Ige, Olusoji Mayowa; Okonji, Patrick E. (Frontiers in Public Health, 2018)
Background: Multi-drug resistant tuberculosis develops through the misdiagnosis, mismanagement and treatment of the disease such as irregular drug supply, poor drug quality, inappropriate prescription and poor adherence to treatment. These factors allow the development and subsequent transmission of a strain of the disease. However, due to the chronic nature of MDR-TB, cure models allow us to investigate the covariates that are associated with the long-term effects of time to sputum conversion among multi-drug resistant tuberculosis individuals. Therefore, this study investigated the survival of tuberculosis patients with the aid of suitable models by predicting the time to sputum conversion. Methods: A retrospective analysis was conducted on 413 records of patients who were diagnosed of multi-drug resistant tuberculosis and met inclusion criteria from April 2012 to October 2016 at the Infectious Disease Hospital, Lagos. The main outcome measure (time to sputum conversion) was the time from the date of MDR-TB treatment to the date of specimen collection for the first of two consecutive negative smear and culture taken 30 days apart. The predictor variables of interest include: demographic (age and gender) and clinical (registration group, number of drugs resistant to at treatment initiation, HIV status, diabetes status and adherence with medication) characteristics. Kaplan-Meier estimates of a detailed survivorship pattern among the patients were examined using Cox regression models. Mixture Cox cure models were also fitted to the data using Log-normal, Log-logistic and Weibull models. The goodness of fit was assessed using the maximum likelihood technique of -2Log likelihood statistic. Results: The patients’ mean age was 36.8±12.7 years and 60.8% were male. About two-third (67.6%) were married. More than half (58.4%) converted to sputum negatives within the duration of study period. Patients who were resistant to <=2 drugs at treatment initiation had 39% rate of conversion than those who were resistant to at least three drugs [HR: 1.39; CI: 0.98, 1.98]. Non-diabetic patients had 23% rate of sputum conversion than diabetic patients [HR: 0.55; CI: 0.24, 0.85]. The overall median time for sputum conversion was 5.5 (IQR: 1.5-11.5) months among those who converted while the median survival time was 7.5 (IQR: 4.0-13.5) months